Virtual reality as an urban tourism destination marketing tool. (20th January 2020) - Moorhouse, Natasha
Although there is a breadth of research demonstrating the effectiveness of virtual reality (VR) as a destination marketing tool, there are limited exploratory studies providing empirical evidence from the perspective of tourism marketers in this specific context. The technological, organisational, environmental (TOE) framework has confirmed explanatory power for studies exploring organisational adoption of various technologies; however, the framework's association with VR research is limited. Responding to this dual gap, this exploratory study explores both internal and external factors associated with VR adoption from tourism marketers' perspectives by employing TOE framework as a theoretical base. Interviews were conducted with seven tourism marketers from three urban tourism destinations in the UK. The preliminary study findings indicate that environmental (perceived competitive pressures and global market appeal) factors are positively associated with tourism marketers' VR adoption, while other TOE factors are not. Finally, theoretical contribution, practical implications and avenues for further research are provided.